“Sentinelle della prateria”: i silos rurali negli Stati Uniti e in Canada* - Barbara Galli, Manuel Vaquero Piñeiro (OS. Opificio della Storia, 2023)
The tall storage elevators that dot the interior plains of North America are part of a carefully planned network for the collection and distribution of grain. The elevators and the small towns adjacent to them were situated by rail-road companies during the late 19th century when the continent’s agricultural heartland was being settled. Increases in agricultural production, a shift in emphasis from domestic to export production, and technological change in grain storage and transportation have produced visible changes in the old system of grain elevators. Today, as in the past, decisions affecting location of grain-storage elevators on the landscape are worked out carefully to minimize transportation costs. In this transformation of the landscape, particular attention has been paid to the definition of construction techniques that have greatly influenced the redesign of the skylines of the American and Canadian prairies.